AB0197 Endothelial dysfunction in a mouse model of SLE: A role for tumor necrosis factor-α?. (23rd January 2014) - Virdis, A.; Tani, C.; Vagnani, S.; Duranti, E.; Bombardieri, S.; Mosca, M.
Abstract : Background: Systemic lupus erythematosus (SLE) is characterized by a reduced endothelium-dependent relaxation. These alteration have been associated with an early occurrence of traditional cardiovascular risk factors as well as to disease related factors such as inflammation and autoantibodies. Objectives: In the present study we aimed to assess the endothelial function on mesenteric resistance arteries in a mouse model of SLE (NZB/W F1) (mSLE) at different disease stages; the endothelial dysfunction (ED) reversibility with anti- tumor necrosis factor (TNF)-α was also investigated. Methods: Twenty 8 weeks old female mSLE were subdivided in 4 groups and monitored for 24-hours proteinuria as disease progression parameter; each group was sacrificed at 12, 18, 24 and 30 weeks of age respectively. Small arteries were studied on a pressurized myograph. E-D relaxation was assessed by infusion of acetylcholine (Ach), NO availability and inflammation were assessed by repeating Ach under the nitric oxide synthase (NOS) inhibitor L-NAME (100 μmol/l) and infliximab (Ifx, monoclonal anti-TNF-α antibody, 100 μmol/l), respectively. C56BL/6J (mC) mice were sacrificed and analyzed at the same age as controls. Results: In mSLE, we observed a decline in relaxation to Ach from 18 weeks of age and a further worsening at 30. The inhibitory effect of L-NMMA on Ach was reduced at 18 and progressively blunted up to 30 weeks; interestingly, ED appeared simultaneously to a significant increase in 24-hours proteinuria (mean 0.39±0.1 at 12 weeks versus 5.8±3.4 at 18 weeks of age, p=0.02). Interestingly, Ifx normalized the relaxation to Ach at 18 and 24 weeks of age but, after that age period, Ifx was no more effective. In mC, maximal relaxation to Ach significantly started to decline at 30 weeks of age with a concomitant reduction of the inhibitory effect of L-NMMA on Ach. Ifx failed to affect the response to Ach at any time. The response to sodium nitroprusside (SNP) was preserved among mC but started to decline at 30 weeks of age in mSLE Conclusions: In this mouse model of SLE we observed a progressive ED caused by a reduced NO availability starting from 18 weeks of age which occurred earlier than in control mice and was concomitant with lupus disease activity. While in mC, ED is related with ageing, in mSLE the inflammatory disease appears to play a role in the development of ED. ED is initially reversed with TNF-alpha blocking but this effect seems to disappear when age-and disease- related vascular structural alterations occur. These data suggest a possible involvement of TNF- alpha on the accelerated atherosclerosis observed in SLE patients Disclosure of Interest: None Declared